PENEGAKAN HUKUM PIDANA BAGI PELAKU USAHA YANG TIDAK MEMILIKI IJIN EDAR MAKANAN Kasus Putusan PN TANJUNG KARANG Nomor 980/Pid.Sus/2020/PN Tjk: PENEGAKAN HUKUM PIDANA BAGI PELAKU USAHA YANG TIDAK MEMILIKI IJIN EDAR MAKANAN Kasus Putusan PN TANJUNG KARANG Nomor 980/Pid.Sus/2020/PN Tjk - doni; Imas Rosidawati Wiradirja; Thariq Muslim; Dhea Alfie; Ery Firsanti; Hodijatussolihah (Program Studi Magister Ilmu Hukum Universitas Islam Nusantara, 2025)
Making a product certainly requires a permit in the process, therefore, to find out the process that needs to be gone through by these business actors, it is necessary to know the systematic flow and the impact if they violate the rules that have been set. Criminal law enforcement by the Food and Drug Supervisory Agency (BPOM) on business actors who market their products will be discussed in more detail. Where many cases occur in Indonesia, business actors do not have distribution permits for food and drugs or are called illegal goods. Government activities in the sector of drug and food distribution supervision in the territory of Indonesia are carried out by BPOM, a non-ministerial central government institution, referring to Presidential Regulation Article 2 Number 80 of 2017. The Center was formed based on the Decree of the Head of BPOM Number 14 of 2014 concerning the Organization of Work Procedures in the BPOM UPT Environment. Every province in Indonesia has a BPOM that helps supervise drugs and food in the region. The purpose of the data collection technique is to find general issues and reliable news. Primary data comes directly from the source, while secondary data is collected through websites, annual reports, and performance reports. This study focuses on the community, BPOM Kepri, and other business actors. The findings of this study are the results of BPOM Kepri's drug and food supervision.